KONTRIBUSI HUTAN RAKYAT AGROFORESTRY TERHADAP PENYERAPAN TENAGA KERJA DAN PENGANGGURAN DI PEDESAAN (Jurnal ForestrIndo, 2024)
The Covid 19 pandemic has had an impact on increasing the number of unemployed in Indonesia as a result of restrictions on people's mobility so that many business activities in various sectors have stopped or laid off some of their workers, except for the agricultural sector which has been relatively least affected by these social restrictions. The agroforestry community forest developed by many people in rural areas, even though it is not a labor-intensive activity, is still capable of absorbing labor, either directly from the farming business or through activities that appear as a trickle-down effect of the agroforestry farming business. The study, which was carried out in three locations, namely Burno Village in Lumajang Regency, Karyasari Village and Karcak Village in Bogor Regency, aims to calculate labor absorption from agroforestry community forestry businesses and related businesses from upstream to downstream (wood plant seed suppliers, wood intermediary traders and the sawmill industry) per hectare of forest and analyzing its possible contribution to reducing unemployment. The study results show that agroforestry community forest can absorb labor of 2.28 people per hectare in Burno Village, 2.08 people per hectare in Karcak Village and 1.93 people per hectare in Karyasari Village. With the results of these calculations, if agroforestry development is carried out on half the area (50%) of the abandoned land in Lumajang Regency which reaches around 12,000 ha, it will be possible to reduce the number of open unemployed by around 45%.